Avaliação da eficiência da moringa oleífera no tratamento de água e de efluentes - GOMES, Emanuelle Regina Araújo (2022)
Among the natural resources available to human beings, water is indispensable for survival. It must undergo treatment processes to be suitable for consumption or other purposes. In this sense, accessible and cheap technologies, such as the use of natural coagulants, like moringa oleifera, can provide access to drinking water. This paper sought to assess the efficiency of the coagulation-flocculation process, using moringa oleifera seeds and a natural biocoagulant based on this plant for the treatment of water and effluents. Water samples were collected from the Cavouco Stream, located in Recife-PE, which receives sewage from hospitals and laboratories, and from textile sewage from the Nossa Senhora do Carmo Laundry, located in Caruaru-PE, assessing the following parameters: pH, Turbidity and Color. Subsequently, the coagulant solution was prepared with the seeds and, through factorial planning 2³, the optimal point of efficiency of the treatment applied for each sample was determined. The analysis of the results was performed with the help of the Pareto Diagram and Response Surface Plots. Statistical significance was observed for the Turbidity and Color parameters in all the assessed samples. However, there was little or no significance for pH. For the results analyzed intra- and inter-methods, it was observed the best removal percentages for the biocoagulant, being verified that this was more efficient for turbidity in sample 1 from the Nossa Senhora do Carmo Laundry and for color in samples 1, 2 and 3 from the Cavouco Stream, being considered more efficient than the coagulant based on moringa seed. Accordingly, the results show that both coagulants can be used in the treatment of water and effluents; however, their best efficiency will be achieved by studying the dosages and will have different behaviors for each type of effluent.